2023
DOI: 10.1038/s41598-023-42975-5
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline depresses facial stimulation-evoked cerebellar MLI-PC synaptic transmission via α2-AR/PKA signaling cascade in vivo in mice

Jun-Ya Wang,
Wen-Cai Weng,
Ting-Qi Wang
et al.

Abstract: The noradrenergic fibers of the locus coeruleus, together with mossy fibers and climbing fibers, comprise the three types of cerebellar afferents that modulate the cerebellar neuronal circuit. We previously demonstrated that noradrenaline (NA) modulated synaptic transmission in the mouse cerebellar cortex via adrenergic receptors (ARs). In the present study, we investigated the effect of NA on facial stimulation-evoked cerebellar molecular layer interneuron (MLI)-Purkinje cell (PC) synaptic transmission in ure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that activation of α 2A -ARs can inhibit adenylate cyclase activity to exert physiological effects through the PKA signaling pathway [ 16 , 17 ]. The catalytic domain of PKA, labeled with enhanced green fluorescent protein (PKAcat-EGFP), is typically localized in highly fluorescent aggregates in the cytoplasm for unstimulated cells [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that activation of α 2A -ARs can inhibit adenylate cyclase activity to exert physiological effects through the PKA signaling pathway [ 16 , 17 ]. The catalytic domain of PKA, labeled with enhanced green fluorescent protein (PKAcat-EGFP), is typically localized in highly fluorescent aggregates in the cytoplasm for unstimulated cells [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In cerebellar cortex, activation of β-AR by a speci c agonist or NE did not directly alter parallel ber-Purkinje cell synaptic transmission, but lowered the threshold for longterm depression induction at parallel ber-Purkinje cell synapses in the occulus through PKA signaling pathway [37]. Under in vivo conditions, NE depresses spontaneous complex spikes activity and the facial stimulation evoked molecular interneuron-Purkinje cell synaptic transmission via AR/PKA signaling pathway in vivo in mice [38,39]. In addition, activation of α-and β-ARs modulated the strength of synaptic transmission and long-term plasticity via cAMP /PKA signaling pathway in the brain [37,[40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%